(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the law, a minor is someone who has not yet reached the age of majority. In many countries, a person becomes an adult at age 18, therefore, a minor is a person who is 17 years old or younger. Today in modern society we can see the country which can be so powerful that they give opportunity to the minors additional guarantees and privileges. This article describes about additional opportunities for the minors.